E-commerce Dispute Resolution Model in Indonesia: ADR (Alternative Dispute Resolution) Perspective - Nur Arisah Mekadina; Iksan; Taufik Firmanto; Zuhrah (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The development of e-commerce in Indonesia has increased digital transaction activities while giving rise to various electronic disputes between consumers and business actors. These disputes have special characteristics, such as the use of electronic contracts, cross-regional transactions, and digital proof, so that conventional litigation mechanisms are considered less effective because they require high costs and a long time. This study aims to analyze the e-commerce dispute resolution model in Indonesia through the Alternative Dispute Resolution (ADR) and Online Dispute Resolution (ODR) approaches. The research method used is a mixed method with normative and empirical approaches. The normative approach is carried out through the study of laws and regulations and legal literature, while the empirical approach is used to understand dispute resolution practices on digital platforms. The results show that adr and ODR are more suitable to be applied in e-commerce disputes because they offer flexibility, cost efficiency, and quick resolution. However, the implementation of ODR in Indonesia still faces regulatory, institutional, transparency, and standard procedural constraints. Therefore, a national ODR model that is integrated with the Indonesian legal system is needed to ensure legal certainty, consumer protection, and the effectiveness of digital dispute resolution.